Assessing the clinical value of faecal bile acid profiling to predict recurrence in primary Clostridioides difficile infection. Issue 11 (17th October 2022) - Mullish, Benjamin H.; Martinez‐Gili, Laura; Chekmeneva, Elena; Correia, Gonçalo D. S.; Lewis, Matthew R.; Horneffer‐Van Der Sluis, Verena; Roberts, Lauren A.; McDonald, Julie A. K.; Pechlivanis, Alexandros; Walters, Julian R. F.; McClure, Emma L.; Marchesi, Julian R.; et al.
Summary: Background: Factors influencing recurrence risk in primary Clostridioides difficile infection (CDI) are poorly understood, and tools predicting recurrence are lacking. Perturbations in bile acids (BAs) contribute to CDI pathogenesis and may be relevant to primary disease prognosis. Aims: To define stool BA dynamics in patients with primary CDI and to explore signatures predicting recurrence Methods: Weekly stool samples were collected from patients with primary CDI from the last day of anti‐CDI therapy until recurrence or, otherwise, through 8 weeks post‐completion. Ultra‐high performance liquid chromatography‐mass spectrometry was used to profile BAs. Stool bile salt hydrolase (BSH) activity was measured to determine primary BA bacterial deconjugation capacity. Multivariate and univariate models were used to define differential BA trajectories in patients with recurrence versus those without, and to assess faecal BAs as predictive markers for recurrence. Results: Twenty (36%) of 56 patients (median age: 57, 64% male) had recurrence; 80% of recurrences occurred within the first 9 days post‐antibiotic treatment. Principal component analysis of stool BA profiles demonstrated clustering by recurrence status and post‐treatment timepoint. Longitudinal faecal BA trajectories showed recovery of secondary BAs and their derivatives only in patients without recurrence. BSH activity increased over time only among non‐relapsing patients ( β = 0.056; likelihood ratio test p = 0.018). A joint longitudinal‐survival model identified five stool BAs with area under the receiver operating characteristic curve >0.73 for predicting recurrence within 9 days post‐CDI treatment. Conclusions: Gut BA metabolism dynamics differ in primary CDI patients between those developing recurrence and those who do not. Individual BAs show promise as potential novel biomarkers to predict CDI recurrence. Abstract : Assessing the clinical value of faecal bile acid profiling to predict recurrence in primary Clostridioides difficile infection.